Clustering and Self‐Recovery of Slanted Hydrogel Micropillars. Issue 24 (17th October 2018) - Lee, Hyemin; Kim, Jun‐Hyun; Wu, Gaoxiang; Lee, Hae‐Min; Kim, Jaekyoung; Kwon, Dokyeong; Yang, Shu; Kim, Chang‐Koo; Yoon, Hyunsik
Abstract: Slanted high‐aspect‐ratio polymer pillars are studied for their unique properties such as unidirectional spreading of liquid, directional adhesions, or alignment of cells, where the pillars are in constant contact with water or in a humid environment. These pillars, however, tend to cluster upon water evaporation due to the capillary force and lowered modulus of the pillars. Here, spontaneous recovery of clustered slanted hydrogel pillars to their original shape is presented by exploiting the modulus change of hydrogel materials during water evaporation. The clustering and recovery of the slanted hydrogel micropillars are monitored in situ by optical microscopy and environmental scanning electron microscopy. To elucidate sequential clustering and recovery mechanism, the adhesion force between the pillars and the restoring force is compared. Finally, the dynamic change of optical transparency is exploited as the result of switching between clustering and recovery of the slanted micropillars for display. The study of the deformation and recovery of slanted hydrogel pillars will offer insights into geometrical and material designs in water‐based applications. Abstract : Sequential clustering and self‐recovery of slanted hydrogel micropillars via in situ monitoring of these events is studied using an optical microscope and an environmental scanning electron microscope, which can be attributed to the change of modulus during water drying from the internal network structure.